PTC behavior of polymer composites containing ionomers upon electron beam irradiation - Kim, JH; Cho, HN; Kim, SH; Kim, JY (POLYMER SOC KOREA, 2004)
We have prepared polymer composites of low-density polyethylene (LDPE) and ionomers (Surlyn 8940) containing polar segments and metal ions by melt blending with carbon black (CB) as a conductive filler. The resistivity and positive temperature coefficient (PTC) of the ionomer/LDPE/CB composites were investigated with respect to the CB content. The ionomer content has an effect on the resistivity and percolation threshold of the polymer composites the percolation Curve exhibits a plateau at low CB content. The PTC intensity of the crosslinked ionomer/LDPE/CB composite decreased slightly at low ionomer content, and increased significantly above a critical concentration ofthe ionomer. Irradiation-induced crosslinking Could increase the PTC intensity and decrease the NTC effect of the polymer composites. The minimum switching current of the polymer composites decreased with temperatures the ratio of I-trip for the ionomer/LDPE/CB composite decreased to a greater extent than that of the LDPE/CB composite. The average temperature coefficient of resistance (alpha(T)) for the polymer composites increased in the low-temperature region.
Keywords: POSITIVE TEMPERATURE-COEFFICIENT; HIGH-DENSITY POLYETHYLENE; CARBON-BLACK; POLY(VINYLIDENE FLUORIDE); CONDUCTIVITY; BLENDS; FILLER; PERCOLATION; PHOSPHATE